2000
DOI: 10.1016/s1071-3581(00)70007-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endothelial dysfunction on regional perfusion in myocardial territories supplied by normal and diseased vessels in patients with coronary artery disease

Abstract: In patients with coronary artery disease, noninvasive measurements of regional myocardial perfusion by Tc-99m sestamibi correlate well with invasive measurements of coronary endothelial function. These findings may have implications for monitoring the effects of interventions designed to improve endothelial function and microvascular function in patients with coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Pathophysiological considerations. The induction of myocardial ischemia is the end result of not only angiographic stenoses but also pathophysiological factors, such as the degree of endothelial dysfunction, which can influence the adequacy of myocardial perfusion during physiological stimulation (27,28) and contribute to the magnitude of perfusion defects observed during exercise MPS (29,30). For this reason, the assessment of myocardial perfusion during stress MPS complements both angiographic measurements (31,32) and Bayesian estimations of ASCAD likelihood in the prediction of cardiac events (1,23).…”
Section: Discussionmentioning
confidence: 99%
“…Pathophysiological considerations. The induction of myocardial ischemia is the end result of not only angiographic stenoses but also pathophysiological factors, such as the degree of endothelial dysfunction, which can influence the adequacy of myocardial perfusion during physiological stimulation (27,28) and contribute to the magnitude of perfusion defects observed during exercise MPS (29,30). For this reason, the assessment of myocardial perfusion during stress MPS complements both angiographic measurements (31,32) and Bayesian estimations of ASCAD likelihood in the prediction of cardiac events (1,23).…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms for a true decrease in perfusion include impairment of diastolic coronary blood flow caused by the abnormal septal post-systolic motion leading to compression of the septal perforators, the phenomenon known as phasic flow [17] and reduced septal endothelial function and reduced coronary flow reserve leading to microvascular dysfunction, reduction in the length of diastole in LBBB (worsening during exercise, leading to reduced perfusion) [18].…”
Section: Nuclear Imagingmentioning
confidence: 99%
“…This systemic endothelial dysfunction is closely related to coronary endothelial dysfunction. 6 Initially, the cold pressor test was used in myocardial perfusion single-photon emission computed tomography (MP-SPECT) tests to induce coronary vasospasm, 7 but recent studies 8,9 have shown its usefulness for the early detection of endothelial dysfunction, since it is a type of stress similar to acetylcholine, inducing an increase in catecholamine levels (epinephrine and norepinephrine) and a rise in blood pressure. 10 Such sympathetic activation causes an increase in coronary blood flow and vasodilation in normal coronary arteries; however, it causes vasoconstriction in the abnormal endothelium.…”
mentioning
confidence: 99%